The Training on Using Formatting Cells And Modifying Cells in Microsoft Excel for Teachers of Pekanbaru Al Fikri Middle School - Endang Istikomah; Fitriana Yolanda; Sari Herlina (UIR Press, 2019)
The activities of the Community aims to increase the knowledge and abilities of Al-Fikri Middle School teachers in the Marpoyan Damai sub-district in the Use of Formating Cells and Modifiying Cells in Microsoft Exel. It is expected that the teachers of Pekanbaru Fikri Middle School can improve their knowledge, abilities and interests in the Use of Formating Cells and Modifiying Cells in Microsoft Exel for both learning and school administration needs. This service was carried out at AL-Fikri Middle School, having its address at Jalan Merak No. 1 Tangkerang Tengah Marpoyan Damai Pekanbaru in the odd semester of TP. 2018/2019. Service methods in the form of lectures, questions and answers and mentoring. The benefits of this activity for mathematics teachers at Al Fikri Pekanbaru Middle School who participated as trainees, can improve their knowledge, abilities and interests in utilizing Microsoft Excel in an effort to improve their pedagogical and professional competencies.